Association of adverse events and associated cost with efficacy for approved relapsed and/or refractory multiple myeloma regimens: A Bayesian network meta‐analysis of phase 3 randomized controlled trials. Issue 12 (10th March 2020) - Dhakal, Binod; Narra, Ravi K.; Giri, Smith; Szabo, Aniko; Smunt, Timothy L.; Ghose, Sanjoy; Pathak, Lakshmi Kant; Aryal, Madan; Hamadani, Mehdi; Chhabra, Saurabh; Janz, Siegfried; D'Souza, Anita; et al.
Abstract : Background: Several new treatment options have been approved for relapsed and/or refractory multiple myeloma (RRMM). In this systematic review, associations of the efficacy of each approved regimen with adverse events (AEs) and the total cost per cycle were compared with a Bayesian network meta‐analysis (NMA) of phase 3 randomized controlled trials (RCTs). Methods: Scopus, Cochrane, PubMed Publisher, and Web of Science were searched from January 1999 to July 2018 for phase 3 RCTs of regimens (approved by the US Food and Drug Administration) used in RRMM. The relative ranking of agents was assessed with surface under the cumulative ranking (SUCRA) probabilities. The primary efficacy, safety, and cost outcomes were progression‐free survival with the regimen, grade 3 to 4 AEs, and the total cost per cycle (regimen cost plus average cost of managing AEs). Results: Fifteen studies including 7718 patients and evaluating 14 different regimens were identified. Daratumumab, lenalidomide, and dexamethasone were ranked highest for reducing progression (hazard ratio, 0.13; 95% credible interval, 0.09‐0.19; SUCRA, 1) but carried the highest probability of total cost per cycle (41, 420; 95% Credible Interval [CrCl], 58, 665‐78, 041; SUCRA, 0.02). Panobinostat, bortezomib, and dexamethasone were the least effective and least safe (SUCRA, 0.24), whereas bortezomib, thalidomide, and dexamethasone emerged as least effective with the highest total cost per cycle (SUCRA, 0.33). Carfilzomib and dexamethasone emerged as the winner when this regimen was considered in terms of efficacy and safety (SUCRA, 0.61) and efficacy and total cost per cycle (SUCRA, 0.60). Conclusions: The results of this NMA can provide additional guidance for the decision‐making process when one is choosing the most appropriate regimen for RRMM. Abstract : Several new treatment options have been approved for relapsed and/or refractory multiple myeloma (RRMM). In this systematic review, associations of the efficacy of each approved regimen with adverse events (AEs) and the total cost per cycle were compared with a Bayesian network meta‐analysis (NMA) of phase 3 randomized controlled trials (RCTs).